Production and localization of beta-fructosidase in asynchronous and synchronous chemostat cultures of yeasts. - Rouwenhorst, R J (1991)
In synchronized continuous cultures of Saccharomyces cerevisiae CBS 8066, the production of the extracellular invertase (EC 3.2.1.26) showed a cyclic behavior that coincided with the budding cycle. The invertase activity increased during bud development and ceased at bud maturation and cell scission. The cyclic changes in invertase production resulted in cyclic changes in amounts of invertase localized in the cell wall. However, the amount of enzyme invertase present in the culture liquid remained constant throughout the budding cycle. Also, in asynchronous continuous cultures of S. cerevisiae, the production and localization of invertase showed significant fluctuation. The overall invertase production in an asynchronous culture was two to three times higher than in synchronous cultures. This could be due to more-severe invertase-repressive conditions in a synchronous chemostat culture. Both the intracellular glucose-6-phosphate concentration and residual glucose concentration were significantly higher in synchronous chemostat cultures than in asynchronous chemostat cultures. In the asynchronous and synchronous continuous cultures of S. cerevisiae, about 40% of the invertase was released into the culture liquid; it has generally been believed that S. cerevisiae releases only about 5% of its invertase. In contrast to invertase production and localization in the chemostat cultures of S. cerevisiae, no significant changes in inulinase (EC 3.2.1.7) production and localization were observed in chemostat cultures of Kluyveromyces maxianus CBS 6556. In cultures of K. marxianus about 50% of the inulinase was present in the culture liquid.